PELAKSANAAN PEMBELAJARAN DARING DENGAN MENGGUNAKAN GOOGLE MEET DAN WHATSAPP PADA MATA PELAJARAN MATEMATIKA - Abdurrasyid Abdurrasyid; Hamdani Hamdani; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research aims to find out and describe the implementation ofonline learning using google meet and whatsapp conducted by teachersin teaching mathematics at Singkawang State Junior High School 4.The research methods used in this study are descriptive. The subjectsin this study were 13 learners. The data collection tools used areobservation sheets, learning outcomes, and questionnaires. Based onthe results of observations, the implementation of online learningcarried out by teachers is mostly in accordance with the learningimplementation plan. Student learning activities in online learning areclassified as inactive with a percentage of 40%. The learning results oflearners in flat side room building materials are classified as highcompletion of at least 75% of 85%. Students' response to theimplementation of online learning using google meet and whatsapp isrelatively positive with a percentage of 73.65%.